LOCALIZED SCALP RASH FOLLOWING RITUXIMAB INFUSION IN AN INFANT WITH ACUTE FLACCID MYELITIS: A CASE REPORT - Anugya Kushwaha; Himanshu Singh; Sapna Meena; Veena Verma; Sparsh Gupta (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Acute Flaccid Myelitis (AFM) is a rare, severe neurological disorder characterized by sudden limb weakness, usually with presumed autoimmune etiology. Immuno-modulatory therapy, including rituximab, is sometimes used off-labely. Cutaneous adverse drug reactions to rituximab can occur but are less frequently reported as localized scalp rashes, particularly in infants. Case Presentation: A 3-month-24-day-old male infant weighing 5kg developed progressive left lower limb monoparesis. Nerve conduction study showed severe axonal and demyelinating neuropathy. MRI and negative CSF PCR showed, anti-AQP4, and anti-MOG antibody confirmed a probable post-viral or autoimmune etiology of AFM diagnosis. The patient was started on intravenous rituximab (100 mg), but within the initial first 10–20 mL of infusion, the infant developed a hypersensitivity reaction. The reaction was erythematous, pruritic maculopapular rash localized to the scalp, with no systemic symptoms. The infusion was immediately stopped, and the rash resolved completely within 48–72 hours following treatment with intravenous antihistaminics and corticosteroids. The adverse drug reaction was subsequently reported to VigiFlow. Conclusion: This report presents a unique, localized cutaneous hypersensitivity reaction to rituximab in an infant, and attention to the importance of careful monitoring during initial infusions and highlighting the value of ADR reporting in paediatric biologics therapy.